Role of cytokines and growth factors in formation and progression of chronic kidney disease in children - I. V. Zorin; A. A. Vyalkova; E. V. Gunkova; L. V. Kutsenko; S. V. Plotnikova; S. A. Tchesnokova; S. M. Konnova (Лечащий Врач)
Analysis of urinary excretion of cytokines and growth factors indicates the prevalence of fibrogenesis inflammation in progression of chronic kidney disease.